2006
DOI: 10.1007/s00428-006-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of primary esophageal synovial sarcoma by demonstration of t(X;18) translocation: a case report

Abstract: Synovial sarcoma (SS) is an uncommon soft tissue tumor occurring mainly in the periarticular region of the extremities of young adults. In this report, we describe a very rare occurrence of primary SS of the esophagus in a 72-year-old woman. Histologically, the tumor demonstrated biphasic morphologic findings associated with poorly differentiated areas. Tumor cells expressed vimentin, epithelial (EMA, CK7, AE1/3), bcl-2 and neuroectodermal (CD56, CD57, CD99) antigens. Differential diagnose included esophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Because this is the first case of a primary synovial sarcoma of the gastrointestinal tract with a subtyping of the translocation, nothing is known about its prognostic relevancy in this context. Similar to other authors [5,7], we suspect that synovial sarcoma of the digestive tract may possibly be an underdiagnosed condition. As cytogenetic and molecular techniques become more accessible for routine testing and awareness of this differential diagnosis grows, the diagnosis of synovial sarcoma in the digestive tract may become more frequent.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Because this is the first case of a primary synovial sarcoma of the gastrointestinal tract with a subtyping of the translocation, nothing is known about its prognostic relevancy in this context. Similar to other authors [5,7], we suspect that synovial sarcoma of the digestive tract may possibly be an underdiagnosed condition. As cytogenetic and molecular techniques become more accessible for routine testing and awareness of this differential diagnosis grows, the diagnosis of synovial sarcoma in the digestive tract may become more frequent.…”
Section: Discussionsupporting
confidence: 49%
“…The gastrointestinal tract is rarely described as a location of synovial sarcomas with few metastatic [4] and isolated cases of primary tumors. We were able to identify 10 cases of primary synovial sarcoma in the gastrointestinal tract described in the literature [5][6][7]: 9 of the esophagus and 1 of the gastric antrum. No data are available on the type of the t(X;18) translocation in these tumors.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported metastases in 50% of those cases, while the 5-year survival is 60.5% (6,12,13). Additionally, some studies have shown a 10-year survival rate ranging between 24 and 68% (6,(12)(13)(14). The most common metastases are found in the lungs, followed by lymph nodes, bone and liver.…”
Section: Discussionmentioning
confidence: 95%
“…In soft tissue synovial sarcoma, numerous studies over the years have reported that it is a high grade malignancy with a high rate of metastasis leading to death; 10-year survival rates between 24% to 68% and 11% to 56% have been reported [27,33]. …”
Section: Discussionmentioning
confidence: 99%